2020
DOI: 10.1101/2020.04.15.20066647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of plasma protein biomarkers related to Alzheimer’s disease, sex and APOE genotype

Abstract: The Australian Imaging and Biomarker Lifestyle (AIBL) study of aging is designed to aid the discovery of biomarkers. The current study aimed to discover differentially expressed plasma proteins that could yield a blood-based screening tool for Alzheimers disease. To search for biomarkers and elucidate mechanisms of AD, we immuno-depleted the most abundant plasma proteins and pre-fractionated the remaining proteins by HPLC, prior to two-dimensional gel electrophoresis. The relative levels of approximately 3,40… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Due to the presence of blood–brain barrier, small molecular compounds in peripheral blood were not used as clinical diagnostic indicators of central nerve injury, for example, NDs, for a long time. In recent years, studies have shown that certain biological macromolecules in peripheral blood are related to nerve damage (Laffoon et al, 2020; Lindbohm et al, 2020). From a metabolomics perspective, there may also be a group of small biomolecules in peripheral blood that are related to nerve injury in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of blood–brain barrier, small molecular compounds in peripheral blood were not used as clinical diagnostic indicators of central nerve injury, for example, NDs, for a long time. In recent years, studies have shown that certain biological macromolecules in peripheral blood are related to nerve damage (Laffoon et al, 2020; Lindbohm et al, 2020). From a metabolomics perspective, there may also be a group of small biomolecules in peripheral blood that are related to nerve injury in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that certain biological macromolecules in peripheral blood are related to nerve damage (Laffoon et al, 2020;Lindbohm et al, 2020). From a metabolomics perspective, there may also be a group of small biomolecules in peripheral blood that are related to nerve injury in the brain.…”
mentioning
confidence: 99%